2021
DOI: 10.3390/biomedicines9101321
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Restraint Stress-Induced Muscle Atrophy Leads to Fatigue in Mice by Inhibiting the AMPK Signaling Pathway

Abstract: Currently, an increasing number of people are suffering from fatigue due to the state of their lifestyles, such as sedentary work in a relatively small space, irregular sleep patterns, or the lack of movement and exercise. The present study was designed to simulate the occurrence of fatigue in the above populations through a chronic restraint stress (CRS) model, and to reveal its dynamic processes and potential underlying molecular mechanisms. ICR mice were subjected to 8 h of restraint stress each day for 5, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 48 publications
6
10
0
Order By: Relevance
“…Consistent with the findings of previous studies, 17,26 we found that body weight, lean body mass, and fat mass were reduced following CRS induction. Although NS did not restore body weight, it increased fat catabolism and attenuated skeletal muscle loss.…”
Section: ■ Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with the findings of previous studies, 17,26 we found that body weight, lean body mass, and fat mass were reduced following CRS induction. Although NS did not restore body weight, it increased fat catabolism and attenuated skeletal muscle loss.…”
Section: ■ Discussionsupporting
confidence: 93%
“…Other studies as well as our previous studies have reported mitochondrial dysfunction in muscle disorders. 17,29 NS treatment protected mitochondria not only from CRS but also from the effects of corticosterone injection. Mitochondrial homeostasis is determined by a dynamic balance between biogenesis and the removal of damaged mitochondria via autophagy.…”
Section: ■ Discussionmentioning
confidence: 91%
See 3 more Smart Citations